A web platform for oral exam of programming class. (15th May 2019) - Kohana, Masaki; Okamoto, Shusuke
We develop a system to help an oral exam for a programming class. Our programming class has a problem about the waiting time for the students. We assume that the waiting time can be reduced when a teacher can check a source code and a result of the program smoothly. A student uploads C++ source codes and registers to a waiting list. The system compiles the code to an HTML and a JavaScript file using Emscripten. The compiled program can run on a web browser. A teacher can check the order of the students for the oral exam. At this time, the teacher also can see the source code and the result. Our system provides a waiting list of the oral exam to keep fairness. Also, the teacher does not overlook an invalid code. It helps a teacher to grade a student correctly.